2020
DOI: 10.1182/bloodadvances.2020002394
|View full text |Cite
|
Sign up to set email alerts
|

Tumor burden, inflammation, and product attributes determine outcomes of axicabtagene ciloleucel in large B-cell lymphoma

Abstract: ZUMA-1 demonstrated a high rate of durable response and a manageable safety profile with axicabtagene ciloleucel (axi-cel), an anti-CD19 chimeric antigen receptor (CAR) T-cell therapy, in patients with refractory large B-cell lymphoma. As previously reported, prespecified clinical covariates for secondary end point analysis were not clearly predictive of efficacy; these included Eastern Cooperative Oncology Group performance status (0 vs 1), age, disease subtype, disease stage, and International Prognostic Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
354
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 336 publications
(375 citation statements)
references
References 50 publications
17
354
2
2
Order By: Relevance
“…Patients with high LDH levels had a worse outcome after treatment with tisa‐cel. Other studies also identified LDH 11 and high tumor volume, measured on CT 29 or PET scan, 14,30 as clear prognostic factors for disease response after CAR T‐cell therapy. Patients with primary refractory disease also had a lower PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high LDH levels had a worse outcome after treatment with tisa‐cel. Other studies also identified LDH 11 and high tumor volume, measured on CT 29 or PET scan, 14,30 as clear prognostic factors for disease response after CAR T‐cell therapy. Patients with primary refractory disease also had a lower PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…on their surface in order to recognize tumor-associated antigens, expanded, and transferred into patients(100,101). CAR-T therapy showed tremendous results for relapsed/refractory B cell hematological malignancies, and CD19-targeted CAR-T therapies have been approved by the FDA (102)(103)(104)(105)(106). Compared to hematological malignancies, the efficacy of CAR-T therapy for solid tumors is limited because of tumorassociated antigen heterogeneity in these, and immunosuppressive factors derived from the tumor microenvironment.…”
Section: Therapy Targeting Emtmentioning
confidence: 99%
“…Decreased tumor burden prior to CAR T-cell infusion is associated with improved efficacy and decreased toxicity in R/R DLBCL ( 10 ). The overall response rate to axi-cel in ZUMA-1, as well as durability of response at 1 year, has been directly associated with lower tumor burden ( 10 , 14 , 41 ). Additionally, there was an association between decreased tumor burden and lower rates of treatment-related toxicity (Grade 3 or higher neurologic events and CRS).…”
Section: Radiation As Bridging Therapy Between Apheresis and Car T Imentioning
confidence: 99%